Dinamika Interaksi Sosial dalam Kelas Bahasa Inggris Virtual: Pendekatan Etnografi Virtual - Hardianti, Hardianti; Irmansyah, Benny (LITERATUS, 2023)
During the COVID-19 pandemic, virtual learning has been applied in the field of education until now. Virtual learning is a new method of learning that certainly provides significant impacts and challenges in English language learning. The impact of virtual learning certainly facilitates the interaction between teachers and students in English classes. As online learning environments become increasingly prevalent, understanding the nuanced social interactions in these settings is crucial. However, virtual learning also provides obstacles in the teaching and learning process. This research employed a virtual ethnographic approach to investigate the dynamics of social interaction within virtual English classes at Esa Unggul University. Through an ethnographic lens, this study delves into the multifaceted nature of interactions among students and lecturers in virtual English classes. Utilizing qualitative data collection methods such as classroom observation, questionnaires, interviews, and analysis of digital communication, shaping social dynamics in the virtual classroom. The findings illuminate the complexities of social interaction, highlighting the role of technology, communication styles, and cultural influences in shaping virtual learning environments. This study's insights contribute to a deeper comprehension of social dynamics in online educational settings and offer valuable implications for optimizing engagement and fostering meaningful interactions in virtual English classes.